(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
The present exploratory study aims to identify the racial biases left by the attachment to retrograde traditions in ballet costumes. Addressing the problem of colors in ballet costumes and the conceptions about what is considered “nude” or “flesh toned”, the research is based qualitatively on concepts of black representation, ballet history and elements of fashion design, based on academic studies and market research. The results present the excluding reality that black dancers live inside ballet, and how dance and textile companies are dealing with these issues nowadays.